Hubungan Pola Asuh Ibu dalam Pemberian Makanan dengan Kejadian Obesitas pada Anak di SD Muhammadiyah 020 Kuok - Saqina, Radyah; Harahap, Dewi Anggriani; Apriyanti, Fitri (Evidence Midwifery Journal, 2024)
Obesity is an excessive accumulation of fat due to an imbalance between the energy intake needed and the energy expended. Factors that cause obesity are genetics, fast food, soft drinks, lack of physical activity, socio-economic and parenting style factors. A child’s eating pattern depends on his parents. If the mother gets used to a healthy eating pattern, the child will get used to it and avoid obesity. The aim of this research was to determine the relationship between maternal parenting patterns in providing food and the incidence of obesity in children at SD Muhammadiyah 020 Kuok in 2023. This type of research is quantitative, analytical in nature with a cross sectional design. The population in this study was all children and parents in grades III, IV, V and VI at SD Muhammadiyah 020 Kuok, namely 95 people. The sample in this study used total sampling. Data collection tools in this research were questionnaires, weight scales and centimeters. Data were analyzed Univariately and Bivariately using the Chi-Square test. The results of research on maternal parenting patterns in providing food to children in the permissive parenting category were 39 (41.1%) mothers and 88 (93.1%) mothers who were not obese. The results of statistical tests showed that there was a relationship between maternal parenting patterns in providing food and obesity in children, p value (0.001). For this reason, it is hoped that mothers will pay more attention to whether the food their children consume is healthy or not so that children avoid obesity